(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With a long history inherited through centuries of business competition, Chinese time-honored brands are a symbol of traditional Chinese culture. As a witness of history, every old Chinese brand is a brand legend, but they are now gradually declining. According to the latest statistics from the Ministry of Commerce of China, only 160 out of over 1,600 “Chinese time-honored brands” have been profitable since 1993. Many time-honored brands are facing the scourge of brand decline or even extinction, with the remaining brands dying at a rate of 5% per year. In recent years, cosmetics have gradually become an inseparable part of people’s daily lives with the increasing income of Chinese residents. China’s broad market prospects have attracted many well-known international brands, while many well-known old Chinese brands have been eclipsed in this increasingly fierce market competition. As the saying goes, “An outsider, however strong, should always respects the locals,” foreign brands have overcome the inherent competitive disadvantages of systems, cultural regions, and the like. In contrast, domestic brands have continued to decline under local advantages, the reasons of which are worth discussing. This article uses Pechoin as an example to explore the development strategies of traditional old brands in the new era and explores the causes of the brand’s resurgence in terms of brand innovation and marketing strategy. Its current problems are discussed to provide a way for other traditional brands to rejuvenate.